Algebra 2 (1st Edition)

Published by McDougal Littell
ISBN 10: 0618595414
ISBN 13: 978-0-61859-541-9

Chapter 7 Exponential and Logarithmic Functions - Chapter Review - Page 542: 34



Work Step by Step

We know that $x\log_ab=\log_ab^x$ and that $\log_ab+\log_ac=\log_a(bc)$ Hence here $\ln x+\ln (x+2)=3\\\ln(x(x+2))=3\\e^3=x(x+2)$ Then using the quadratic formula we get: $x=\frac{-2\pm\sqrt{(-2)^2-4(1)(-e^3)}}{2(1)}=\frac{-2\pm\sqrt{4+4e^3}}{2}=-1\pm\sqrt{1+e^3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.